2013
DOI: 10.3109/13880209.2013.767360
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect ofCnestis ferrugineaand its active constituent on scopolamine-induced memory impairment in mice: A behavioral and biochemical study

Abstract: Context: Cnestis ferruginea Vahl ex DC (Connaraceae) (CF) is used in traditional African medicine in the management of CNS disorders. The degeneration and dysfunction of cholinergic neurons is closely associated with the cognitive deficits of Alzheimer's disease (AD) and oxidative stress has been implicated in its pathogenesis. However, the influence of C. ferruginea on the cholinergic system and oxidative stress parameters has not been explored. Objective: The present study investigates the effect of methanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 45 publications
5
22
0
Order By: Relevance
“…AD is a neurodegenerative disease with complex pathology, involving cholinergic deficit and intracellular oxidative stress. SCOP, a nonselective muscarinic Ach receptor antagonist, blocks cholinergic transmission in the central nervous system and produces cognitive dysfunction, including long‐term and short‐term memory impairment (Ishola et al, ). SCOP also influences the brain oxidative status, which is imbalanced in AD, making the SCOP‐induced amnesia model relevant in screening and investigating antiamnesic agents.…”
Section: Discussionmentioning
confidence: 99%
“…AD is a neurodegenerative disease with complex pathology, involving cholinergic deficit and intracellular oxidative stress. SCOP, a nonselective muscarinic Ach receptor antagonist, blocks cholinergic transmission in the central nervous system and produces cognitive dysfunction, including long‐term and short‐term memory impairment (Ishola et al, ). SCOP also influences the brain oxidative status, which is imbalanced in AD, making the SCOP‐induced amnesia model relevant in screening and investigating antiamnesic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the above results, 500 mg/kg SS administration was selected as a moderate dose for the scopolamine induced memory impairment experiment in this study. The passive avoidance test is generally used to evaluate memory in three steps (learning acquisition, memory retention, and the retrieval process) (Ishola et al, ). The SS improved learning and memory abilities as well as attenuated scopolamine induced amnesia mice.…”
Section: Discussionmentioning
confidence: 99%
“…[59,60] Scopolamine has been found to increase oxidative stress and impaired the anti-oxidative defense system. [61,62] Many clinical studies have reported strong evidence that oxidative stress in involved in the pathogenesis of Alzheimer's disease. The oxygen free radicals are implicated in the process of age related decline in the cognitive performance may be responsible for the development of Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%